The Influence of Occupation, Socio-Economics, History of Sexually Transmitted Diseases and Health Insurance Participation on Visual Inspection with Acetic Acid Visits in Ponorogo Regency - Sari, Riska Permana; Azam, Mahalul; Rustiana, Eunike Raffy (Public Health Perspective Journal, 2021)
Cervical cancer is a type of cancer that affects women of reproductive age. The incidence of cervical cancer in the world is in the second position which is a major problem of women's health, in developing countries especially in Indonesia. Health workers have been intensively taking preventive measures to reduce the high prevalence of cervical cancer in Indonesia. Precautions can be taken by action the early detection method is simple, namely visual inspection with acetic acid (VIA). This study aims to analyze the factors that influence the efforts of women of childbearing age to carry out early detection of cervical cancer using the visual inspection with acetic acid method. This research is a quantitative study with a case control study approach. A sample of 150 respondents consisting of 50 case samples and 100 control samples were obtained by using a 2-stage sampling technique, namely cluster random sampling and proportionated random sampling. Data analysis used chi square test and logistic regression. The results showed that the p value of occupation (p = 0.047), socio-economics (p = 0.138), history of sexually transmitted diseases (p = 0.318), health insurance participation (p = 0.007). The conclusion of this study is that there is an influence between occupation and health insurance participation against visual inspection with acetic acid visits.